Pembuatan Direktori Lokasi Selancar di Sumatera Barat - Aditya, Aditya; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discusses about creation Directories Surfing Locations in West Sumatera. The purpose of this paper is to describe directories surfing locations in West Sumatra. The method used is: observation, interview and literature study to find out the surf as well as an explanation of what is contained in surfing locations in West Sumatra. Based on data analysis, summarized as follows. First, based on the findings in the field is known that there are 13 surfing locations in West Sumatra. Locations Â in different cities such as Padang, Pariaman, Pesisir Selatan and Mentawai islands, each location has a characteristic of each. Second, the limitations of the study in the manufacture directory surfing locations in West Sumatra that is making the site plan that was the starting point is the City Padang. Third, because the locations are far enough away from the city of Padang that the authors make the plan as possible so that users can read the information the floor plan.Keyword: Directories, Location, Surfing, West Sumatera.